2016
DOI: 10.1177/2050640615588024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon dioxide insufflation in balloon‐assisted enteroscopy: A systematic review and meta‐analysis

Abstract: Background and aim: The efficacy of CO 2 insufflation during balloon-assisted enteroscopy remains controversial. This study aimed to perform a systematic review with meta-analysis of randomized controlled trials (RCTs) in which CO 2 insufflation was compared with air insufflation in balloon-assisted enteroscopy. Methods: PubMed, the Cochrane library, and the Igaku-Chuo-Zasshi database were searched to identify RCTs eligible for inclusion in the systematic review. Data from the eligible studies were combined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…its impact on patient comfort and insertion depth [239 -242]. A systematic review with meta-analysis by Nishizawa et al [243] has recently analyzed 4 RCTs (2 on DBE and 2 on SBE; 461 patients overall, 235 randomized to undergo enteroscopy with air and 226 with CO 2 insufflation) that aimed to evaluate the impact of CO 2 in DAE procedures. When compared with air, use of CO 2 insufflation significantly increased the insertion depth for antegrade enteroscopy, but not for the retrograde approach.…”
Section: Recommendationmentioning
confidence: 99%
“…its impact on patient comfort and insertion depth [239 -242]. A systematic review with meta-analysis by Nishizawa et al [243] has recently analyzed 4 RCTs (2 on DBE and 2 on SBE; 461 patients overall, 235 randomized to undergo enteroscopy with air and 226 with CO 2 insufflation) that aimed to evaluate the impact of CO 2 in DAE procedures. When compared with air, use of CO 2 insufflation significantly increased the insertion depth for antegrade enteroscopy, but not for the retrograde approach.…”
Section: Recommendationmentioning
confidence: 99%
“…Statistical analysis was conducted using the Review Manager (RevMan; The Cochrane Collaboration, 2008; The Nordic Cochrane Centre, Copenhagen, Denmark). We used a random-effects model and Mantel-Haenszel method to calculate the odds ratio (OR), and we used inverse variance for the continuous data to estimate the weighted mean difference (WMD) with 95% confidence intervals (CI) [12]. Heterogeneity in the results of the studies was assessed by Cochran's Q and I 2 tests.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a systematic review with meta-analysis was performed in 2016 5 , where the depth of intubation, abdominal pain, and CO 2 retention were analyzed, not all other outcomes or subgroups that the present review was able to list and analyze.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that many studies have already compared the use of ambient air and CO 2 in the various endoscopic procedures, and recently 2 systematic reviews with meta-analysis 5 6 have shown outcomes that have been analyzed in subgroups and that were not previously analyzed. On this premise, this systematic revision is conducted to substantiate the comparison of the use of CO 2 in relation to conventional air using the information available in the literature from randomized clinical trials (RCTs) already performed.…”
Section: Introductionmentioning
confidence: 99%